FORMULASI SEDIAAN SABUN CUCI TANGAN CAIR DARI MINYAK KELAPA MURNI (VIRGIN COCONUT OIL) - Ginting, Ferdinand Paulus; Alfian Rejekinta Munthe; Nettietalia Br Brahmana; Maudina Audila Sam (Universitas Sari Mutiara Indonesia, 2021)
Virgin coconut oil is a modification of the manufacture of coconut oil so as to produce a product with a lower water content and acid content, with a clear color. The purpose of this study was to determine the formulation of liquid hand soap preparations using virgin coconut oil (VCO). The sample used in this study is old coconut which will be processed into pure coconut oil VCO (Virgin Coconut Oil). This research method was carried out experimentally, the processing of virgin coconut oil was carried out using the inducement method. The main ingredients used in the formulation of soap preparations are virgin coconut oil and potassium hydroxide using a stirrer. From the research results it is known that virgin coconut oil VCO (Virgin Coconut Oil) can be used as a basic ingredient for liquid hand soap formulations and inhibits the antibacterial activity of Staphylococcus aureus at a concentration of 3% with an inhibition zone of 2.75 mm, a concentration of 6% with an inhibition zone of 5, 50 mm and a concentration of 9% with an inhibition zone of 9.75 mm. Pure coconut oil liquid hand soap VCO (Virgin Coconut Oil) has antibacterial activity against Staphylococcus aureus bacteria.